Social Displacement in The Global Era in Baek Se-Hee’s Novel - Setiowati, Titik; Thohiriyah, Thohiriyah (Universitas Negeri Semarang, 2024)
This study analyzes the phenomenon of social displacement occurs in society in the global era as reflected in Baek Se-Hee's memoir